Antonio Gaudí - Teshigahara, Hiroshi; Segawa, Junichi; Segawa, Ryu; Yanagida, Yoshikazu (The Criterion Collection, 2020)
Catalan architect Antonio Gaudí (1852-1926) designed some of the world s most astonishing buildings, interiors, and parks; Japanese director Hiroshi Teshigahara constructed some of the most aesthetically audacious films of the second half of the twentieth century. Here, their artistry melds in a unique, enthralling cinematic experience. Less a documentary than a visual poem, Teshigahara's "Antonio Gaudí" takes viewers on a tour of Gaudí's truly spectacular architecture, including his massive still-unfinished masterpiece, the Sagrada Familia cathedral, in Barcelona. With camerawork as bold and sensual as the curves on his subject's organic surfaces, Teshigahara immortalizes Gaudí on film. [Cover]